2013
DOI: 10.1063/1.4813280
|View full text |Cite
|
Sign up to set email alerts
|

High-speed atomic force microscope combined with single-molecule fluorescence microscope

Abstract: High-speed atomic force microscopy (HS-AFM) and total internal reflection fluorescence microscopy (TIRFM) have mutually complementary capabilities. Here, we report techniques to combine these microscopy systems so that both microscopy capabilities can be simultaneously used in the full extent. To combine the two systems, we have developed a tip-scan type HS-AFM instrument equipped with a device by which the laser beam from the optical lever detector can track the cantilever motion in the X- and Y-directions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 47 publications
0
60
0
Order By: Relevance
“…The use of fluorescence-related microscopy can help us to discern the detailed subcellular structures (e.g., cytoskeletons, cellular nuclei, cytoplasm) during the AFM indenting; thus, it greatly complemented the indentation by AFM. In addition, researchers have successfully combined high-speed AFM with fluorescence microscopy in the recent researches [82][83][84]. Suzuki et al [82] combined high-speed AFM with an optical fluorescence microscope by developing a tip-scanning system, and the results (observing the dynamics of living cells) showed that this system can remarkably improve the time resolution.…”
Section: Challenge and Outlookmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fluorescence-related microscopy can help us to discern the detailed subcellular structures (e.g., cytoskeletons, cellular nuclei, cytoplasm) during the AFM indenting; thus, it greatly complemented the indentation by AFM. In addition, researchers have successfully combined high-speed AFM with fluorescence microscopy in the recent researches [82][83][84]. Suzuki et al [82] combined high-speed AFM with an optical fluorescence microscope by developing a tip-scanning system, and the results (observing the dynamics of living cells) showed that this system can remarkably improve the time resolution.…”
Section: Challenge and Outlookmentioning
confidence: 99%
“…Suzuki et al [82] combined high-speed AFM with an optical fluorescence microscope by developing a tip-scanning system, and the results (observing the dynamics of living cells) showed that this system can remarkably improve the time resolution. Fukuda et al [83] have combined high-speed AFM with total internal reflection fluorescence microscopy, and this system can perform simultaneous topographic and fluorescence imaging at the single molecule level. Colom et al [84] have developed a hybrid high-speed atomic forceoptical microscope for visualizing single-membrane proteins on eukaryotic cells, allowing high-speed AFM imaging about 1,000 times faster than conventional AFM/ optical microscopy setups.…”
Section: Challenge and Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…More seriously, the cantilever blocks the optical path of fluorescence microscopy. To overcome this problem, tip-scan HS-AFM has been developed, in which the laser beam of the OBD detector is steered with a two-dimensional mirror tilter to track the lateral motion of the cantilever (Fukuda et al 2013). This system has been combined with total internal reflection fluorescence microscopy.…”
Section: Hybrid Hs-afm/optical Microscopy Systemmentioning
confidence: 99%
“…One of the common requirements of tip-scan AFM that employs the widely used optical lever method of detecting cantilever's deflection is that the laser beam focused onto the cantilever should be able to track the lateral motion of the cantilever. This tracking adoptable to tip-scan HS-AFM was recently accomplished by laser beam scan in synchrony with the cantilever's lateral motion using either a mirror tilter 20 or a focusing lens embedded in the XY-scanner. 21 The combined system of total internal reflection fluorescence microscopy (TIRFM) and tip-scan HS-AFM equipped with the mirror tilter was demonstrated to be able to capture topographic AFM and single-molecule fluorescent images simultaneously at a few frames/s (fps).…”
Section: Introductionmentioning
confidence: 99%